PGE2 Desensitizes β-Agonist Effect on Human Lung Fibroblast-Mediated Collagen Gel Contraction through Upregulating PDE4 - Qiuhong Fang; Yingmin Ma; Jing Wang; Joel Michalski; Stephen I. Rennard; Xiangde Liu (Mediators of Inflammation)
In the current study, we investigated the effect of a long-acting β-agonist (salmeterol) and a phosphodiesterase 4 (PDE4) inhibitor (cilomilast) on human lung fibroblast-mediated collagen gel contraction. Higher concentrations of salmeterol (10−7 and 10−6 M) inhibited fibroblast-mediated collagen gel contraction. No effect was observed with cilomilast alone (up to 10−5 M). In the presence of 10−8 M salmeterol, however, cilomilast could significantly inhibit fibroblast-mediated collagen gel contraction in a concentration-dependent manner (10−7~10−5 M). Blockade of endogenous PGE2 by indomethacin further potentiated the inhibitory effect of salmeterol on fibroblast-mediated collagen gel contraction, but it did not affect cilomilast's effect. Pretreatment with PGE2 abolished the inhibitory effect of salmeterol, but it potentiated the inhibitory effect of cilomilast on fibroblast-mediated collagen gel contraction. Finally, indomethacin slightly inhibited PDE4C expression, while PGE2 stimulated the expression of PDE4A and -4C in human lung fibroblasts. These findings suggest that long-acting β-agonist and PDE4 inhibitor have a synergistic effect in regulating fibroblast tissue repair functions and that PGE2 can modulate the effect of β-agonist and PDE4 inhibitor at least in part through the mechanism of regulating PDE4 expression.